Molecular and Conventional Analysis of Acute Diarrheal Isolates Identifies Epidemiological Trends, Antibiotic Resistance and Virulence Profiles of Common Enteropathogens in Shanghai - Yang, Feng; Jiang, Yonggen; Yang, Lihua; Qin, Juanxiu; Guo, Mingquan; Lu, Yuxia; Chen, Hongyou; Zhuang, Yuan; Zhang, Jinghao; Zhang, Hong; Dai, Zhaoyun; Li, Min; et al. (Frontiers in Microbiology, 2018)
Objective: To investigate prevalence of acute diarrhea in Shanghai and analyze virulence associated-genes and antibiotic resistance of major enteropathogens using combination of conventional and molecular epidemiology methods. Method: The 412 stool specimens were obtained by systematic sampling from diarrhea patients throughout entire year 2016. Bacterial and viral pathogens were identified and bacterial isolates were cultured and screened for antibiotic resistance profiles. Two most prevalent bacteria, Vibrio parahaemolyticus and Salmonella were further typed by multi-locus sequence typing (MLST) and analyzed for presence of virulence-associated genes. The association between virulence genes, resistance phenotypes and genetic diversities was analyzed. Results: Among stool specimens testing positive for pathogens (23.1%), 59 bacterial and 36 viral pathogens were identified. V. parahaemolyticus (27/412, 6.6%), Salmonella (23/412, 5.6%) and norovirus GII (21/412, 5.1%) were three most-commonly found. Most bacterial isolates exhibited high levels of antibiotic resistance with high percentage of MDR. The drug resistance rates of V. parahaemolyticus and Salmonella isolates to cephalosporins were high, such as 100.0% and 34.8% to CFX, 55.6% and 43.4% to CTX, 92.6% and 95.7% to CXM, respectively. The most common resistance combination of V. parahaemolyticus and Salmonella was cephalosporins and quinolone. The dominant sequence types (STs) of V. parahaemolyticus and Salmonella were ST3 (70.4%) and ST11 (43.5%), respectively. The detection rates of virulence genes in V. parahaemolyticus were tlh (100%) and tdh (92.6%), without trh and ureR. Most of the Salmonella isolates were positive for the Salmonella pathogenicity islands (SPIs) genes (87%-100%), and some for Salmonella plasmid virulence (SPV) genes (34.8% for spvA and spvB, 43.5% for spvC). In addition, just like the drug resistance, virulence genes exhibited wide-spread distribution among the different STs albeit with some detectable frequency linkage among Salmonella STs. Conclusion: Bacterial infections are still the major cause of severe diarrheas in Shanghai. The most common bacteria V. parahaemolyticus and Salmonella show molecular characteristics consistent with preselection of highly virulent types with exceedingly high level of antibiotic resistance. Key words: Acute diarrhea, Epidemiology, Pathogens, Resistance, multilocus sequence type (MLST), Virulence